Analysis of the status of providing specialized medical and preventive care to nephrological patients in Ukraine in 2020 - Kolesnyk, M.O.; Kozlyuk, N.I.; Razvazhaeva, O.O. (Ukrainian Journal of Nephrology and Dialysis, 2021)
Objective: rating evaluation of specialized medical and preventive care for renal patients in different regions of Ukraine and Kyiv in 2020 using the method of complex statistical coefficients. Methods. The basis for rating determination was the analysis of the components of specialized medical care for nephrological patients. The source of information was the data from the National Register of Patients with Chronic Kidney Disease and Patients with Acute Kidney Injury in 2020. Results. The rating of the regions of Ukraine and Kyiv in terms of specialized medical and preventive care for nephrological patients in 2020 has been determined. Conclusions: The status of specialized medical and preventive care for nephrological patients during 2020 has worsened in 13, in 5 remained unchanged, and only in 7 regions has improved. It is necessary to plan at least a 3-year program of implementation of governmental and regional measures to improve specialized medical and preventive care for nephrological patients.